Prevalence of enterotoxigenic Bacteroides fragilis in patients with colorectal cancer: a systematic review and meta-analysis - Xia, Shijun; Ma, Lijuan; Li, Hui; Li, Yue; Yu, Linchong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe gut microbiome, specifically enterotoxigenic Bacteroides fragilis (ETBF), has been reported to play a role in colorectal cancer development. We aimed to conduct a systematic review and meta-analysis of published studies to compare the prevalence of ETBF in patients with colorectal cancer and healthy controls as well as in various stages of colorectal cancer.MethodsPubMed, EMBASE, and The Cochrane Library were systematically searched for studies published until May 2024. We utilized studies either comparing the prevalence of ETBF in patients with colorectal cancer and healthy control or examining its prevalence across different stages of colorectal cancer. The prevalence of ETBF colonization in biological samples from individuals with colorectal cancer compared to that in healthy controls or adjacent normal tissue as well as the association between the prevalence of ETBF and various stages of colorectal cancer were plotted using a random-effect or fixed-effect model.ResultsFourteen relevant articles were identified. Meta-analyses revealed that patients with colorectal cancer had a higher likelihood of having ETBF than healthy controls (odds ratio [OR]: 2.54, 95% confidence interval [CI]: 1.63–3.98, I2 = 55%). Additionally, ETBF detection was lower in stage I/II than in stage III/IV colorectal cancer (OR: 0.61, 95% CI: 0.41–0.91, I2 = 41%).DiscussionThe prevalence of ETBF was consistently higher in the tissue and fecal samples of patients with colorectal cancer than in those of controls. A difference in ETBF prevalence between stage I/II and stage III/IV colorectal cancer was noted, but further analysis revealed that the conclusion is unreliable.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD 42024548325.